2023
DOI: 10.1177/01492063221143721
|View full text |Cite
|
Sign up to set email alerts
|

Green by Affiliation? Ownership Identity and Environmental Management System Adoption in Chinese Business Groups

Abstract: How does owner identity affect environmental management system (EMS) adoption by business group affiliates? While current research on EMS adoption is mostly focused on stand-alone Western firms, a marked uptake of adoption has unfolded in Eastern countries such as China, where business group affiliates are the dominant organizational form. This stark contrast between corporate interest and research attention has left a clear lacuna in our understanding of how systems that can reduce environmental impact diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 118 publications
(168 reference statements)
0
6
0
Order By: Relevance
“…Finally, the surprising finding that ownership does not influence GSCM practice adoption provides new evidence to the literature about the link between domestic ownership and environmental practice adoption (Balasubramanian et al, 2021;Wang et al, 2023;Zhu, Cordeiro, & Sarkis, 2012). Previous findings showed that foreignnon-Chinese-owned firms were more engaged in environmentally proactive actions than Chinese firms (Zhu, Cordeiro, & Sarkis, 2012).…”
Section: Implications For Researchmentioning
confidence: 76%
“…Finally, the surprising finding that ownership does not influence GSCM practice adoption provides new evidence to the literature about the link between domestic ownership and environmental practice adoption (Balasubramanian et al, 2021;Wang et al, 2023;Zhu, Cordeiro, & Sarkis, 2012). Previous findings showed that foreignnon-Chinese-owned firms were more engaged in environmentally proactive actions than Chinese firms (Zhu, Cordeiro, & Sarkis, 2012).…”
Section: Implications For Researchmentioning
confidence: 76%
“…According to Eesley and Lenox (2006) and Diestre and Rajagopalan (2014), these risks may take the form of litigation, fines, and stakeholder dissatisfaction that may curtail the viability of INVs, business group affiliates, and MNEs alike. In the same vein, Wang, Heugens, and Wijen (2023) write that foreign ownership has a positive effect on business group affiliates' propensity to adopt environmental management systems. This finding is doubly pertinent as foreign investors have discretion and may choose to disengage from governance activities (Han, Ding, and Zhang 2022), such as environmental commitment.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, the peculiarity of the current finding resides in the distinctive role of FO as opposed to domestic ownership. Moreover, the inherent finding suggests that FO in INVs is akin to FO in business group affiliates (Wang, Heugens, and Wijen 2023) and foreign institutional ownership (FIO) in MNEs (Ellimäki et al 2023). To quote the latter, “FIOs drive their investee firms [the MNEs] to improve environmental performance in order to reduce reputational and legal risks” (Ellimäki et al 2023, 923).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowledge sharing (Lee, Choo & Yoon, 2016;Lee & MacMillan, 2008;Lee, MacMillan & Choe, 2010;Lee, Lee & Gaur, 2017) and social capital (Yiu, Hoskisson & Lu, 2003) impacts of affiliation have been examined to a lesser extent. Several studies focus on business group affiliated firms; however, they do not make a distinction between within group and outside group relations of affiliates (Kang & Lee, 2017;Lee, Yang & Park, 2020;Wang, Heugens & Wijen, 2023).…”
Section: Introductionmentioning
confidence: 99%